Counselling Skills for Health Professionals - Burnard, Philip. author. aut Link
VIII, 264 p.
Keywords: This is the second edition of a book that I hope continues to be of practical value. For counselling must always be that: practical. No amount of talking, on its own, can really make a difference if people do not end up doing something as a result of counselling. The practical thread remains an important one throughout this edition. Counselling Skills for Health Professionals is not just a 'how to do it' book: people are probably too complicated for that approach to be of much use. Counselling is never simply a matter of learning a range of skills which you then apply in a range of settings. In the end, counselling is about facing the person in front of you, listening to them carefully and then supporting them as they work through their problems. For many problems, there are no easy answers and counselling doesn't offer any 'quick fixes'. It is essentially a supportive process. There are many things it cannot do. It cannot change certain social and political situations. It cannot cure diseases. On the other hand, what it can do is offer people more hope. Often, just the fact that there is somone who is prepared to hear your story and to listen to you is all that is needed. I remain convinced that the key issue in all types of counselling is the ability to listen.